Comparative assessment of early-ripening soybean cultivars and samples in the conditions of the northern Volga region - I. Yu. Ivanova; A. A. Fadeev; S. V. Ilina (Аграрная наука Евро-Северо-Востока, 2024)
The purpose of the research was to study promising soybean cultivars from the collection of the N. I. Vavilov All–Russian Institute of Plant Genetic Resources (VIR) of various ecological and geographical groups in the conditions of the Chuvash Republic (northern Volga Region of the Volga Federal District of the Russian Federation) and identify sources of breeding valuable traits for their further use in hybridization. Under observation, study and comparison were 161 samples of the VIR collection and 40 cultivars of Russian and foreign breeding (Belarus, Canada, USA, Germany, Poland, Ukraine, Austria, Sweden, etc.).  The ‘SibNIIK-315’ cultivar approved for cultivation in the Volga-Vyatka region (Russia) was taken as the standard. The research was carried out in 2021–2023 in the field on a natural background (gray forest heavy loamy soil). According to the productivity of one plant in the very early ripening group the ‘Memory Fadeeva’ and ‘Kasatka’ (Russia) cultivars had the best indicators of 17.0 g, in the early ripening group it was ‘Doka’ (Russia) with 18.0 g and sample 1029/2 (Poland) with 18.5 g. The productivity of the standard cultivar was 14.1 g/plant, LSD05 = 2.6 g. According to the seed size the following promising cultivars were identified: ‘Lumaria’ and ‘Belgorodskaya 7’ (Russia), which had maximum weight of 1000 seeds of 206g and 186 g, respectively, that was 41g and 21 g more than the standard cultivar, LSD05 = 12.6 g. As to the height of attachment of the lower bean, 8 samples and three cultivars were positively characterized. They had the placement of the upper layer of beans to the soil surface more than 17 cm, that was 6 cm higher than this indicator for the standard cultivar, with LSD05 = 5.4 cm.  All the studied source material was highly resistant to phytopathogens and lodging. The cultivars identified during the research process are valuable source material for the development of new highly competitive soybean varieties of the northern ecotype for cultivation in conditions of 56o north latitude.